2002
DOI: 10.1098/rspb.2002.1971
|View full text |Cite
|
Sign up to set email alerts
|

Facial attractiveness judgements reflect learning of parental age characteristics

Abstract: Mate preferences are shaped by infant experience of parental characteristics in a wide variety of species. Similar processes in humans may lead to physical similarity between parents and mates, yet this possibility has received little attention. The age of parents is one salient physical characteristic that offspring may attend to. The current study used computer-graphic faces to examine how preferences for age in faces were influenced by parental age. We found that women born to 'old' parents (over 30) were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 64 publications
4
74
1
1
Order By: Relevance
“…A side effect of developmental plasticity in the face processing regions of the brain may bias mate choice towards specific familial traits. As children are exposed to the faces of their parents more than those of other adults, these characteristics may be particularly important in influencing mate preferences ( Perrett et al 2002). However, as we have seen, familiarity, in itself, is not likely to lead individuals to search for a partner who fits their parents' mental template.…”
Section: R E T R a C T E Dmentioning
confidence: 85%
See 1 more Smart Citation
“…A side effect of developmental plasticity in the face processing regions of the brain may bias mate choice towards specific familial traits. As children are exposed to the faces of their parents more than those of other adults, these characteristics may be particularly important in influencing mate preferences ( Perrett et al 2002). However, as we have seen, familiarity, in itself, is not likely to lead individuals to search for a partner who fits their parents' mental template.…”
Section: R E T R a C T E Dmentioning
confidence: 85%
“…Using a computer-graphic method, it was found that women born to 'old' parents (over 30) were more attracted to older faces than those born to younger parents, and men's preferences for female faces were R e t r a c t e d influenced by their mother's age and not their father's age in a long-term relationship (Perrett et al 2002). A study that examined hair and eye colour of male and female participants, their partners and their parents found positive correlations between parental characteristics and actual partner characteristics (Little et al 2002b).…”
Section: Introductionmentioning
confidence: 99%
“…They arise for a number of reasons, such as parental influence, sexual history, and self-perceived attractiveness (Jennions & Petrie, 1997;Perrett et al, 2002;Pfaus, Kippin, & Centeno, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…In other words, why would some men and women choose lower-quality markers over higher-quality markers? Speculation as to how individual differences develop include learning and differences in life history Perrett et al 2002), self-perceived attractiveness and hormonal shifts (PentonVoak & Perrett 2000). Our findings do not elucidate the mechanisms influencing individual differences, rather they offer more enticing evidence for their existence and appeal for further investigation.…”
Section: Discussionmentioning
confidence: 99%